2010
DOI: 10.1136/gut.2010.208314
|View full text |Cite
|
Sign up to set email alerts
|

The NSAID sulindac is chemopreventive in the mouse distal colon but carcinogenic in the proximal colon

Abstract: These data show that the sulindac diet promotes carcinogenesis in the mouse proximal colon possibly through chronic inflammation. Sulindac has both beneficial and harmful effects in vivo, which are associated with different microenvironments within the colon of experimental mice. Deficiency for the Msh2 or p53 tumour suppressor genes increases the harmful side effects of long-term sulindac treatment in the mouse colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 46 publications
6
58
0
Order By: Relevance
“…This is consistent with clinical practice, where colon and rectal cancers are treated as distinct entities (47), and a growing body of evidence that associations between dietary patterns, chemoprotective nonsteroidal anti-inflammatory drugs (NSAIDs), and CRC risk differ across anatomic subsites (21,37). In contrast, a recent comprehensive molecular characterization of human colon and rectal cancer demonstrated that after excluding hypermutated cancers, colon and rectal cancers appear to have similar patterns of genomic alteration (40).…”
mentioning
confidence: 73%
“…This is consistent with clinical practice, where colon and rectal cancers are treated as distinct entities (47), and a growing body of evidence that associations between dietary patterns, chemoprotective nonsteroidal anti-inflammatory drugs (NSAIDs), and CRC risk differ across anatomic subsites (21,37). In contrast, a recent comprehensive molecular characterization of human colon and rectal cancer demonstrated that after excluding hypermutated cancers, colon and rectal cancers appear to have similar patterns of genomic alteration (40).…”
mentioning
confidence: 73%
“…Recently, it is reported that the effect of a nonsteroidal anti-inflammatory agent sulindac inhibited tumorigenesis in the distal colon in a murine model. However, it augmented carcinogenesis in the proximal colon in mismatch repair-deficient mice, suggesting that depending on the oncogenic changes, differential responses are noted in the colon [35].…”
Section: Discussionmentioning
confidence: 98%
“…Since disease susceptibility of the colon exhibits an anatomical bias with respect to dietary risk factors and chemoprevention (Mladenova et al, 2011; Hjartaker et al, 2013; Parr et al, 2013), the effect of nutritional combinations on intestinal biology is typically assessed in both the proximal and distal colon. Due to the low level of apoptosis in non-carcinogen treated mice, the apoptotic index is expressed as the total number of apoptotic cells per 100 crypts as previously reported (Davidson et al, 2012), instead of per crypt column.…”
Section: Discussionmentioning
confidence: 99%